2007
DOI: 10.1016/j.leukres.2007.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TCL-1 as a potential prognostic factor for treatment outcome in B-cell chronic lymphocytic leukemia

Abstract: TCL-1 expression is variable in CLL, and no study has examined its association with treatment response. We measured TCL-1 protein in CLL cells from 51 patients who then received pentostatin, cyclophosphamide, and rituximab. TCL-1 expression did not correlate with any pre-treatment characteristics. Lower TCL-1 levels were associated with higher probability of attaining flow cytometry-negative status post-treatment (52% versus 17%, p=0.046). Trends toward improved complete remission rate (49% versus 19%, p=0.064… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…However, high TCL-1 expression strongly associated to aggressive disease features, such as higher white blood cell counts and shorter duplication time (Herling et al, 2009). In agreement with these data, two independent studies have shown that high TCL-1 expression correlates with worse disease outcome (Herling et al, 2009), while low TCL-1 expression showed a trend toward improved complete remission rate after treatment (Browning et al, 2007). In agreement with these data, Enzler and coworkers (Enzler et al, 2009) have found that CLL-like cells from the IgH-E-Tcl-1 transgenic mice have also high proliferation rates.…”
Section: The Igh-e-tcl-1 Transgenic Mouse As a Model Of Aggressive Cllsupporting
confidence: 63%
“…However, high TCL-1 expression strongly associated to aggressive disease features, such as higher white blood cell counts and shorter duplication time (Herling et al, 2009). In agreement with these data, two independent studies have shown that high TCL-1 expression correlates with worse disease outcome (Herling et al, 2009), while low TCL-1 expression showed a trend toward improved complete remission rate after treatment (Browning et al, 2007). In agreement with these data, Enzler and coworkers (Enzler et al, 2009) have found that CLL-like cells from the IgH-E-Tcl-1 transgenic mice have also high proliferation rates.…”
Section: The Igh-e-tcl-1 Transgenic Mouse As a Model Of Aggressive Cllsupporting
confidence: 63%
“…24,25 We have previously described that TCL1 shows a differential and regulated expression pattern in CLL, 20 and an association of high protein levels of TCL1 with features of aggressive disease in CLL has been subsequently indicated by us and others. 20,26,27 We show here that the growth stimulatory effects of BCR engagement in CLL cultures are strongly correlated with the levels of TCL1 and the kinetics of TCL1-AKT recruitment to BCR membrane complexes. Increased TCL1 levels are also strongly associated with inferior clinical outcome, independent of treatment.…”
Section: Introductionmentioning
confidence: 68%
“…Human CLL has been characterized as having multiple epigenetic defects that include abnormal methylation and silencing of genes. One oncogene, TCL1, is generally over-expressed in CLL and is associated with poor response to therapy (13). The E-TCL1 transgenic mouse model of CLL shows characteristics similar to the human disease, with an initial expansion of non-clonal B lymphocytes at approximately 3 months followed by progression to a mature B-cell leukemia at 9-11 months (11).…”
Section: Resultsmentioning
confidence: 99%